Evaluation of the Influence of CYP2C9* 2, CYP2C9*3 Gene Polymorphisms on the Efficacy and Safety of Postoperative Analgesia with Ketoprofen in Patients after Cardiac Surgery - T. E. Morozova; D. A. Shatsky; N. V. Shikh; E. V. Shikh; T. B. Andrushchyshina; M. V. Lukina; A. A. Kachanova; Zh. A. Sozaeva; G. N. Shuev; N. P. Denisenko; E. A. Grishina; D. A. Sychev (Столичная издательская компания, 2021)
Aim. The aim of the study was to evaluate the efficacy and safety of ketoprofen as an analgesic therapy in patients with CYP2C9*2 (430C>T) rs179985 and CYP2C9*3 (1075A>C) rs1057910 gene polymorphisms after cardiac surgery.Material and methods. The study included 90 patients. Postoperative analgesia was perfomed by ketoprofen 100 mg intramuscularly twice daily. The evaluation of pain was determined daily by Numeric Rating Scale for 5 days after cardiac surgery. The safety of ketoprofen was determined by assessing the severity of gastroenterological symptoms using the Gastrointestinal Symptom Rating Scale questionnaire and determining the frequency of episodes of acute kidney injury. The material for DNA was venous blood. To determine the single nucleotide genetic polymorphisms CYP2C9*2 (430C>T) rs179985 and CYP2C9*3 (1075A>C) rs1057910, the real-time polymerase chain reaction was used.Results. In patients with the AA genotype of CYP2C9*3 polymorphism, the intensity of pain on the numeric rating scale scale (points) was significantly higher than in patients with the AC genotype: 7 [6; 8] vs 6 [5; 6] (р=0,003), 7 [6; 8] vs 6 [5; 6] (р=0,04), 6 [5; 7] vs 5 [4; 5] (р=0,04), 5 [3; 6] vs 3 [3; 4] points (р=0,02) on days 1, 2, 3 and 5 of the postoperative period, respectively. The severity of gastroenterological symptoms was higher in patients with a heterozygous CT genotype for the allelic variant CYP2C9*2 than in patients with a wild CС genotype and amounted to 19 [19; 22] vs 18 [16; 20] points, respectively, (p=0,04). The distribution of genotypes for CYP2C9*2 polymorphisms and CYP2C9*3 polymorphisms between the groups of acute renal injury did not differ significantly.Conclusion. Associations of polymorphisms CYP2C9*3 with a lower intensity of pain syndrome and CYP2C9*2 with a greater severity of gastroenterological symptoms were revealed.